65.0k views
2 votes
Solve for a in : 2(3a + 1) = 11a =

1 Answer

5 votes

Step-by-step explanation

Since we have the expression 2(3a+1) = 11, applying the distributive property:

6a + 2 = 11

Subtracting -2 to both sides:

6a = 11 -2

Subtracting numbers:

6a = 9

Dividing both sides by 6:

a = 9 / 6

Simplifying:

a = 3 / 2

In conclusion, the value of a is 3/2

User Ofir Israel
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.